The Influence of Health Education on Community Knowledge about the Dangers of Smoking in the Working Area of the Paal Merah I Community Health Center, Jambi City in 2024 - Andriyanti, Elisa; Putri, Amelia Gustina; Shyafaatsya, Vifany Sellsa; Yantoni, Lara Syafrila Wil; Oktavanie, Marshelly Ghea; Bachtiar, Najwa; Noerjoedianto, Dwi (Journal of Midwifery and Nursing, 2024)
Smoking is a bad habits that can have a bad impact on your own health and that of others. Cigarettes are wrapped tobacco products that come from plants such as Nicotiana tabacum and Nicotiana rustica, or they can also be synthetic products containing nicotine and tar, with or without the addition of other ingredients. This research aims to determine the effect of health education on public knowledge about the dangers of smoking in the Paal Merah I Community Health Center Working Area, Jambi City in 2024. This research uses the Wilcoxon test which shows that there is a significant difference between before and after the education was implemented. These findings confirm that health education is effective in increasing public knowledge about the dangers of smoking. Using a semi-experimental method, this research involved a pretest and posttest on 19 respondents selected from three areas that had the highest smoking rates, namely RT.11, RT. 25, and RT.35 Paal Merah Village. The results of the normality test showed that the data was not normally distributed, which means there was a correlation between before the counseling was carried out and after the counseling was carried out. Thus, health education efforts have the potential to change smoking behavior and contribute to efforts to prevent tobacco-related diseases. It is hoped that the intervention steps taken will help reduce the prevalence of smoking at the household level and improve overall public health in the area.